Issues and Methodology for Development of Transgenic Fish for Aquaculture with a Focus on Growth Enhancement - Robert H. Devlin; Peter A. Raven; L. Fredrik Sundstr¨om; Mitchell Uh (Blackwell Publishing, 2025)
The advent of gene transfer methods in model mammalian species in the early 1980s (Palmiter et al. 1982; Hammer et al. 1985a) provided impetus to genetically engineer a range of other vertebrates for applied purposes. In particular, the remarkable enhancement in growth rate of mice to transgene-derived overexpression of growth hormone (GH) led to extensive transgenic studies in mammals for terrestrial agricultural species (Pursel et al. 1989). For domesticated mammals, transgenesis resulted in only modest growth acceleration (compared to effects in mice) and some improvements in feed utilization, but were also associated with significant pleiotropic metabolic, physiological, and morphological abnormalities (Pursel et al. 1989; Rexroad et al. 1989; Pursel et al. 1997; Rozycki et al. 1999; Pursel et al. 2004; Adams and Briegel 2005). Thus, this technology has not been applied in commercial agriculture, although research to overcome some of these obstacles continues.